CONFIDENTIALITY AS A FUNDAMENTAL PRINCIPLE OF LAWYERS’ ACTIVITIES - Litvinova, Iryna; Kolonska, Viktoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study confidentiality as a fundamental principle of a lawyer’s activities, as well as the ability of lawyers to use electronic technologies and artificial intelligence when providing legal assistance to their clients in order to comply with the principles of confidentiality in legal activities. Research methods: general scientific and special methods of scientific knowledge were used, the use of which made it possible to describe the principle of confidentiality in the practical activities of lawyers. Results: the research shows that in cases where artificial intelligence functions are used when providing legal assistance, it is recommended to provide a separate provision in the contract on whether the client allows the lawyer to use artificial intelligence technologies when providing legal assistance, and to what extent. However, in order to comply with the principle of confidentiality in legal activities, not only the defense attorney, but also the client must ensure non-disclosure of information to other users when using information technologies. Discussion: a feature of the legal profession is that lawyers receive information from their clients that they should not disclose to other persons under any circumstances or that they are obliged to keep secret. The client’s trust in the lawyer arises only if the lawyer observes the principle of confidentiality. The principle of confidentiality in legal practice is directly enshrined in Ukrainian legislation and is fundamental. Digital technologies and artificial intelligence have a direct impact on the behavior of lawyers and their clients, as well as on the effectiveness of their response to the needs of clients under legal aid contracts. The Internet provides instant access to all information and offers opportunities for rapid exchange of information. However, there are also risks, such as unauthorized use of personal data and loss of monopoly on information ownership.